Low-voltage coded excitation utilizing a miniaturized integrated ultrasound system employing piezoelectric 2-D arrays - Triger, Simon (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2010)
We describe the development of an integrated, miniaturized ultrasound system designed for use with low-voltage piezoelectric transducer arrays. The technology targets low-frequency NDT and medium- to high-frequency sonar applications, at 1.2 MHz frequency. We have constructed a flexible, reconfigurable, low cost building block capable of 3-D beam forming. The tessellation of multiple building blocks permits formation of scalable 2-D macro-arrays of increased size and varying shape. This differs from conventional ultrasound solutions by integrating the entire system in a single module. No long RF cables are required to link the array elements to the electronics. The close coupling of the array and electronics assists in achieving adequate receive signal amplitudes with differential transmission voltages as low as +/- 3.3 V, although the system can be used at higher voltages. The system has been characterized by identifying flat-bottomed holes as small as 1 mm in diameter located at depths up to 190 mm in aluminum, and holes as small as 3 mm in diameter at a depth of 160 mm in cast iron. The results confirm the ability of the highly integrated system to obtain reflections from the targets despite the +/- 3.3 V excitation voltage by exploiting coding in low-voltage ultrasound